MEMÓRIA TELEVISIVA COMO PRODUTO CULTURAL: um estudo de caso das telenovelas no Canal Viva - Fernandes, Julio Cesar (2013)
This research is aimed at studying the television memory, recovered and built by a pay-TV channel, Canal Viva, and the telenovelas from TV Globo displayed by the channel concerned, in order to verify its characteristics as a cultural product and its place in the plot of mediation and social interactions. In order to do so, the following theoretical bases are established, relating them to the concept of memory: culture, identity, imagination, history of TV and the Brazilian telenovelas, television reception (with a focus on mediation) and nostalgia. For this purpose, the methodology, as built-up, is divided into two steps: first, a bibliographic research and then a case study, on which techniques of documentary analysis are applied, guided interviews with representatives from the channel and, finally, a focus group with assiduous viewers of the Canal Viva telenovelas. The goal of this research is to contribute to studies on communication related to television memory, thus affirming its importance in social interactions.